Medical congresses and other scientific and professional meetings during the COVID-19 pandemic: КОНГРЕСИ И COVID-19 (PONS - medicinski časopis, 2020)
PONS Medical Journal traditionally reports on scientific and professional congresses and meetings in medicine that are of potential interest to our physicians and nurses. However, the current pandemic COVID-19 has introduced almost dramatic changes in the organization of these events both in the world and in our country. That is why the usual articles about medical scientific and professional meetings in this issue of the PONS medical journal were missing. Instead, this article analyzes the current challenges in our country and in the world in this area, opportunities and strategies for overcoming them and their future impact on the organizers and participants of congresses and other scientific, professional and educational medicine in medicine.